Malaysian Butterfly Lizard Leiolepis triploida (Reptilia, Squamata: Leiolepidae) in Clearwater Sanctuary, Perak: geographical range extension in Peninsular Malaysia - Yong, Hoi Sen; Yap, Ken; Belabut, Daicus Martin; Lim, Phaik Eem; Lee, C.K. (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2011)
The Malaysian Butterfly Lizard Leiolepis triploida is known from the inland areas of Perlis, Kedah and Seberang Perai (Penang) in the northwestern part of Peninsular Malaysia. The present finding of this butterfly lizard in Clearwater Sanctuary, Batu Gajah, Perak Darul Ridzuan has extended its known geographical range further south in Peninsular Malaysia. It remains to be established how far south it would spread, how widespread it is in Peninsular Malaysia, and whether it would displace the existing populations of the Common Butterfly Lizard Leiolepis belliana.